2005
DOI: 10.1016/j.actaastro.2004.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory correction manoeuvres in the transfer to libration point orbits

Abstract: In this paper we study the manoeuvres to be done by a spacecraft in order to correct the error in the execution of the injection manoeuvre in the transfer trajectory. We will consider the case in which the nominal trajectory is a halo orbit around the collinear equilibrium point L 1 . The results can be easily extended to the L 2 point and to other kinds of libration point orbits, such as Lissajous and quasi-halo orbits. For our study we use simple dynamical systems concepts related with the invariant manifold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In this section we address the so called first trajectory correction maneuver (TCM1), that is the one responsible for the correction of the errors introduced in the execution of the initial departure maneuver, ∆v, due to the inaccuracies of the thruster. The analysis follows a similar approach to the one in [11] for the transfer from a parking orbit around the Earth to a LPO around the equilibrium point L 2 of the Sun-Earth system, ignoring navigation errors. Contrary to other more general approaches for TCMs, like the ones of Qi & de Ruiter [28], focusing in tracking a previous defined transfer trajectory, the approach we follow focuses in the determination of a new LPO target orbit, which someway measures the sensitivity of the transfer problem in terms of the variation of the final LPO orbit with respect to an injection error.…”
Section: Preliminary Study Of the Tcm1mentioning
confidence: 99%
See 1 more Smart Citation
“…In this section we address the so called first trajectory correction maneuver (TCM1), that is the one responsible for the correction of the errors introduced in the execution of the initial departure maneuver, ∆v, due to the inaccuracies of the thruster. The analysis follows a similar approach to the one in [11] for the transfer from a parking orbit around the Earth to a LPO around the equilibrium point L 2 of the Sun-Earth system, ignoring navigation errors. Contrary to other more general approaches for TCMs, like the ones of Qi & de Ruiter [28], focusing in tracking a previous defined transfer trajectory, the approach we follow focuses in the determination of a new LPO target orbit, which someway measures the sensitivity of the transfer problem in terms of the variation of the final LPO orbit with respect to an injection error.…”
Section: Preliminary Study Of the Tcm1mentioning
confidence: 99%
“…Of course, the earlier the first TCM is planned, the better it will be.Next we consider the influence of the initial velocity error ε on the cost of the TCM. According to[11], and using a simplified RTBP as dynamical model, the relation between the magnitude of the local optimal correction ∆V * TCM and the initial velocity error ε is linear. In this work we have obtained similar results using the full ephemeris model.…”
mentioning
confidence: 99%
“…A sensible contribute in the study of transfer orbits to libration points through manifold exploitation has been given by Koon, Lo et al [18] [19], Gómez et al [12] [13], Starchville and Melton [23] [24]; this strategy has revealed its effectiveness in the design of low-energy transfers to the Moon.…”
Section: Introductionmentioning
confidence: 99%